Application of three-dimensional (3D) reconstruction in the treatment of video-assisted thoracoscopic complex segmentectomy of the lower lung lobe: A retrospective study - Wang, Xinyu; Wang, Qing; Zhang, Xindi; Yin, Hang; Fu, Yujie; Cao, Min; Zhao, Xiaojing (Frontiers in Surgery, 2022)
Background An increasing number of lung ground-glass nodules (GGNs) have been detected ever since low-dose computer tomography started growing in popularity. Three-dimensional (3D) reconstruction technology plays a critical role in lung resection, especially in segmentectomy. In this study, we explore the role of 3D reconstruction in thoracoscopic complex segmentectomy of lower lung lobe. Methods A total of 97 patients who underwent complex segmentectomy of lower lung lobe from January 2021 to March 2022 were retrospectively analyzed. We divided these patients into a 3D group (n = 42) and a routine group (n = 55) based on preoperative 3D reconstruction or without this procedure. The demographics of patients and GGNs were collected and perioperative outcomes were compared between the two groups. Results All of the baseline characteristics between the groups were comparable (all P > 0.05). There was no 30-day postoperative mortality and conversion in the two groups. The operation time of the 3D group was significantly shorter than that of the routine group (111.4 ± 20.8 min vs. 127.1 ± 32.3 min, P = 0.007). The number of stapler reloads during surgery in the 3D group was less than that in the routine group (9.0 ± 2.2 vs. 10.4 ± 2.6, P = 0.009). The rate of air leakage on postoperative days 1–3 was lower in the 3D group (11.9% vs. 30.9%, P = 0.027). In addition, the resection margins of all patients in the 3D group were adequate, while four patients in the routine group had inadequate resection margins, although there was no statistically significant difference (P = 0.131). Intraoperative blood loss, postoperative drainage, postoperative hospital stay, pneumonia/atelectasis, and hemoptysis were similar between the two groups. Conclusions For performing complex segmentectomy of the lower lung lobe, the procedure of 3D reconstruction may shorten the operation time, decrease the number of stapler reloads, prevent postoperative air leakage, and guarantee a safe surgical margin. Therefore, 3D reconstruction is recommended for complex segmentectomy of the lower lung lobe.